Ensuring the Stability of Channel Linings Under Unsteady Filtration - Fayziev , Kh.; Khojiyev , T.K.; Rakhimov , Sh.A.; Zhuraev , K.T.; Khalikov , M.B. (International Journal of Membrane Science and Technology, 2023)
When assessing the stability of the slopes of the banks of reservoirs and channels, the filtration regime that occurs with a rapid decrease in the water level in the upstream, which is due to the nature of the operation of structures before floods, discharges, emergency situations, is of particular interest. A change in the water levels in the upstream causes a change in the position of the depression surface and the parameters of the filtration flow (pressure gradients, filtration rates and flow rates) in the coastal massif. At the same time, unsteady filtration occurs in the coastal massif and the stability of the slopes is reduced significantly due to the action of hydrodynamic forces directed towards the slope. The most reliable anchors of channel slopes in similar conditions are those that, under normal channel operation, when there is no groundwater support, the lining should exclude filtration from the channel, ie filtration losses of irrigated water, and if there is a backwater and with a rapid decrease in the water level in the channel, it should provide free access of the ground stream into the channel channel or its diversion in the other direction. This eliminates the occurrence of significant hydrodynamic pressures, and the destruction of the channel slope fasteners. The article presents the results of studies of 4 designs of channel linings operating under conditions of unsteady filtration. In the course of the study, we considered the following variants of structural schemes of linings. Fastening with combined deformation and filtration seams; fastening with self-collapsing seams; fastening with discharge tubular drains with water discharge into the channel; fastening with filtration and discharge holes arranged during the appearance of groundwater backup in the channel area. The results of calculating the stability of the fastening plates for overturning and surfacing are presented. According to the results of the calculation, the most acceptable fastening options are determined, their advantages and disadvantages are given. The proposed fastening design meets the above requirements and thereby ensures the strength and stability of the linings during the operation of the channel.